Case Report: Favorable Response to the Tyrosine Kinase Inhibitor Apatinib in Recurrent Merkel Cell Carcinoma - Feng, Yiyi; Song, Xin; Jia, Renbing (Frontiers in Oncology, 2021)
Background: As angiogenesis is an essential step in tumor growth and metastasis, the tyrosine kinase inhibitor (TKI) apatinib has become a revolutionary anticancer therapy across various malignancies. However, its efficiency and safety in Merkel cell carcinoma (MCC) are uncertain. Case presentation: The current study described the case of a 91-year-old man who presented with a 3.2×3.0×2.2 cm rapidly growing, solitary tumor of the right lower eyelid. It was diagnosed as MCC pathologically. Twenty-seven days after the surgery, the patient returned to the hospital with recurrent MCC. Apatinib was then administered to this patient. The patient had a complete response (CR) to apatinib after 4.4 months of targeted therapy. Twenty-seven months of progression-free survival (PFS) was achieved with controllable treatment-related adverse events (AEs). Conclusion: Treatment with apatinib demonstrated clinical benefit in our patient with recurrent MCC, highlighting its potential utility in other MCC patients. Further clinical trials are needed to determine the efficacy and safety of apatinib in MCC patients.